Influence of a Low‐Carbohydrate High‐Fat Diet on Peritoneal Inflammation, Cancer‐Associated Lymphocytes, and Survival in a Murine Carcinomatous Peritonitis Model. Issue 6 (12th September 2020) - Watkins, Ayako; Fukatsu, Kazuhiko; Higashizono, Kazuya; Watanabe, Tomoki; Noguchi, Midori; Tominaga, Eiji; Murakoshi, Satoshi; Yasuhara, Hiroshi
Abstract: Background: Low‐carbohydrate high‐fat diets (LCHFDs) are thought to be beneficial for metabolic support in patients with advanced cancer. However, whether LCHFDs affect the progression of carcinomatous peritonitis (CP) remains unclear. Our study examined the influence of a lard‐based LCHFD on host immunity and survival in a murine CP model. Methods: Mice were fed either a normal diet (ND) or an LCHFD ad libitum. On day 7, Panc02 cancer cells were inoculated intraperitoneally. Mice were killed on days 7, 21, and 35, and cytokine levels in the peritoneal fluid, as well as the number and phenotypes of peritoneal, splenic, and tumor‐infiltrating lymphocytes were measured. Survival studies were performed with both ad libitum and isocaloric feeding in other sets of mice. Results: The levels of all cytokines significantly increased in the LCHFD group compared with those in the ND group on day 21. The tumor necrosis factor α and interleukin‐10 levels were higher in the LCHFD group than in the ND group on day 35. In the LCHFD group, the regulatory T‐cell (Treg) number was significantly higher in the peritoneal cavity and tumor. The survival times were worse in the LCHFD group than in the ND group. Conclusion: The ad libitum, lard‐based LCHFD feeding of CP mice increases the peritoneal cytokine levels, which may reduce splenic, anticancer lymphocytes and increase the number of Tregs in the peritoneal cavity and tumor. The detrimental effects of LCHFD are linked to dietary composition rather than overfeeding.